Role of Market Liquidity in Sentiment-Based Return Predictions: Evidence from Sri Lanka - Dissnayake, D. M. T. R.; Nanayakkara, N. S. (International Journal of Economics and Financial Issues, 2025)
Behavioural finance theories contend that market anomalies, driven by human biases and heuristics, link liquidity to investor sentiment in asset markets. The irrational investor underreaction increases liquidity and explains the time-series relationship between liquidity and market returns. Based on data from the Colombo Stock Exchange (CSE), this study examines the extent to which market-wide illiquidity and sentiment proxied by turnover measure can forecast the short-term expected returns of the frontier market Sri Lanka during the period 2010-2021, using OLS time series regression methodology. Research findings show that investor sentiment proxied by turnover is positively related to expected market returns, contrary to the observations based on the US market. Regression estimates indicate that expected illiquidity significantly negatively impacts expected returns in a value-weighted specification. Unexpected illiquidity shocks depress the contemporaneous market returns. Small-cap stock returns show greater sensitivity to market illiquidity indicating that they face greater illiquidity risk compared to large-cap stocks. These findings offer insight into how investor sentiment can influence market liquidity and the impact of liquidity risk pricing on market returns over time in a frontier market.